Piazza Montanelli: Il luogo ritrovato, Fucecchio (FI) - ARX architetti > Heliopolis 21 (AND Rivista di architetture, città e architetti, 2020)
The project derives from an Ideas Competition organized by the Municipality of Fucecchio, open to possible visions of regeneration of this vital part of the city and won by the studios Arx Srl and Heliopolis 21.